Du dialogue entre études littéraires et cultural studies - Grall, Catherine (Verbum – Analecta Neolatina, 2012)
How can cultural studies and literary studies dialogue? After a short summary of the history of cultural studies, this paper insists upon the transdisciplinarity of the field, seen both as an advantage and as a weakness. Its common points with other sciences — in the same way as comparative literature has common points with other fields — make it an interesting domain and produce powerful notions but also reveal a paradigmatic lack. Only a veritable open-minded dialogue between cultural studies and literary studies devoid of any ideological globalizing views can lead to an interesting epistemological feedback for literary sciences in our time, as literature seems more and more concerned with concrete, social and global issues.